Upaya Meningkatkan Hasil Belajar Ips dengan Menggunakan Metode Pembelajaran Learning Start with a Question pada Peserta Didik Kelas VII-A MTS Miftahul Jannah Palangka Raya: Efforts to Improve Ips Learning Outcomes by Using Learning Start with a Question Learning Methods in Class VII-A MTS Miftahul Jannah Palangka Raya Students - Tarwiyah, Tarwiyah; Wibowo, Setyo (Neraca: Jurnal Pendidikan Ekonomi, 2019)
This study aims to find out: (1) How to increase the learning activities of students when using the learning method of Learning Start With a Question (LSQ) on social studies learning in class VII-A MTs Miftahu Jannah Palangka Raya, (2) Is there an increase in social studies learning outcomes students after using the learning method Learning Start With a Question (LSQ) in class VII-A MTs Miftahul Jannah Palangka Raya. The research method used in this study is the Classroom Action Research (CAR) method. The research subjects were class VII-A MTs Miftahul Jannah Palangka Raya with subjects as many as 24 students. Data collection techniques in this study used observation and tests. Data analysis techniques are based on the results of each learning process cycle. The results of this study are: (1) an increase in learning activities when using the Learning Start With a Question (LSQ) learning method for students of class VII-A MTs Miftahul Jannah Palangka Raya Tahun to be better, namely the score of learning activities of students in the first cycle Individuals have 15 students who get a score of ≥ 75, and 9 students who score <75 with an average score of 2.67. Scores of learning activities of students in the second cycle there were 23 students who obtained a score of ≥ 75, and 1 student who scored <75 with an average of 3.86, so that the learning activities of students in the second cycle had been categorized as good or already achieving indicators of success, (2) There is an increase in social studies learning outcomes after using the Learning Start With a Question (LSQ) learning method for students of class VII-A MTs Miftahul Jannah Palangka Raya. This can be seen from the data on student learning outcomes during the pre test obtaining an average value of 30.20 with completeness in classical 0%. Post test cycle I obtained an average score of 78.95 with completeness in classical 62.5%, and in cycle II increased with an average value of 90.41 with classical completeness 95.83%.